Pneumococcal Surface Protein A Is Expressed In Vivo, and Antibodies to PspA Are Effective for Therapy in a Murine Model of Pneumococcal Sepsis - Swiatlo, E. (American Society for Microbiology, 2003)

(untitled)
Pneumococcal surface protein A (PspA) is an immunogenic protein expressed on the surface of all strains of Streptococcus pneumoniae (pneumococcus) and induces antibodies which protect against invasive infection in mice. Pneumococci used for infectious challenge in protection studies are typically collected from cultures grown in semisynthetic medium in vitro. The purpose of these studies is to confirm that PspA is expressed by pneumococci during growth in vivo at a level sufficient for antibodies to PspA to be protective. Mice were actively immunized with purified PspA or by passive transfer of monoclonal antibody (MAb) and challenged with a capsular type 3 strain in diluted whole blood from bacteremic mice. All were protected against challenge with 10 times the 50% lethal dose (LD(50)), and mice challenged with 1,000 times the LD(50) had increased survival compared with controls. Additionally, nonimmune mice treated with MAbs to PspA or PspA immune serum at 6 and 12 h after infection with 10 times the LD(50) also showed increased survival. Northern blot analysis of RNA from pneumococci grown either in vitro or in vivo showed similar levels of PspA mRNA. These results demonstrate that PspA is expressed in vivo in a mouse model and that immunization with PspA induces antibodies to an antigen which is expressed during the course of invasive infection. Immunotherapy with antibodies to PspA may have some utility in treating pneumococcal infections in humans.